Glucose abnormalities in Asian patients with chronic hepatitis C - Bo Q; Orsenigo R; Wang J; Griffel L; Brass C (Dove Medical Press, 2015)
Qingyan Bo,1 Roberto Orsenigo,2 Junyi Wang,1 Louis Griffel,3 Clifford Brass3 1Beijing Novartis Pharma Co. Ltd., Shanghai, People’s Republic of China; 2Novartis Pharma AG, Basel, Switzerland; 3Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA Abstract: Many studies have demonstrated a potential association between type 2 diabetes (T2D) and hepatitis C virus infection in Western countries, while similar evidence is limited in Asia. We compared the prevalence of glucose abnormalities (impaired fasting glucose [IFG] and T2D) and their risk factors between Asian and non-Asian chronic hepatitis C (CHC) patients, and evaluated whether glucose abnormalities impacted the viral responses to peginterferon plus ribavirin treatment (current standard of care in most Asian countries). This study retrospectively analyzed data of 1,887 CHC patients from three Phase II/III studies with alisporivir (DEB025) as treatment for CHC. The chi-square test was used to compare the prevalence of IFG/T2D between Asian and non-Asian CHC patients, and logistic regression was used to adjust for sex, age, and cirrhosis status. Risk factors for IFG/T2D were evaluated using univariate and multivariate analysis. Our results indicated that the prevalence of IFG/T2D was high in both Asian and non-Asian CHC patients (23.0% vs 20.9%), and no significant difference was found between these two populations (adjusted odds ratio: 1.3, 95% confidence interval: 0.97, 1.7; P=0.08). Age, sex, and cirrhosis status were risk factors for IFG/T2D in both populations, while body mass index was positively associated with IFG/T2D in non-Asian but not in Asian participants. No significant differences in sustained virological response rates were seen between patients with normal fasting glucose and patients with IFG/T2D for both populations. These results demonstrate that the prevalence of glucose abnormalities in Asian CHC patients was similar to that in non-Asians, and glucose abnormalities had no impact on viral response to peginterferon plus ribavirin. Keywords: CHC, type 2 diabetes, risk factor, alisporivir